(3Jbjje COGA bWGY UfGYI GdSjGQGJ ai LeghQjI LfhH GaQjbjG efP YGe (B1994/ s - (3SjO YHOGdQMef CMeO eMeOs; (3fgdI CMeO CHhGdYR (B: s; (3ghjOG YHOGdYXje YHOGdgGOi (B: s ((3GdbGgQI (B: s (3SjO YHOGdQMef CMeO eMeO (B: s, 2019)
(3jbhe bWGY UfGYI GdSjGQGJ HOhQkG gGekG ai GdJfejI GdGbJUGOjI deG jMJGLg gPG GdbWGY ef QGS eGd VNe h YeGdI eGgQI h eOQHI h JcfhdhLjG YGdjI h fJjLI YOe JhGaQ gPg GdGdjGJ dOi GdYOjO ef GdOhd GdfGejI afdGMX SjWQJ YOO eMOhO ef GdOhd Ydi (B62% (3ef GfJGL gPg GdUfGYI Mhd GdYGde h gi GdhdGjGJ GdeJMOI GdGeQjcjI h GdUjf h GdjGHGf h GdeGfjG h GdgfO(B: (3h JSYi LfhH GaQjbjG Ydi GSJMhGP fSHI (B1% (3ef GdShb GdYGdejI dGfJGL GdSjGQGJ MJi JVef eSGMI Ydi GdSGMI GdYGdejI(B. (3h fJjLI dPdc SYJ LeghQjI LfhH GaQjbjG Gdi JfejI GdbWGY dNaV eYOdGJ GdYLR ai GdejRGf GdJLGQi GdfGJL Yf GSJjQGO GdSjGQGJ h ef Ke GdGQJbGA HeYOdGJ Gdfeh GdGbJUGOi h Ndb GdeRjO ef aQU GdYed h JMbjb GdYOGdI ai JhRjY GdONhd h GdKQhGJ h gi GgOGa GdSjGSI GdUfGYjI HYO YGe (B1994: (3h SYJ LfhH GaQjbjG GdONhd Gdi GdGShGb GdYGdejI Yf WQjb YOO ef GdHQGeL h GdSjGSGJ JJeKd ai (B(1) (3HQfGeL JfejI h JWhjQ bWGY UfGYI GdSjGQGJ (B((3Ee Bi Oi Hi(B) (3h GdPi HOC JWHjbg YGe (B1994: (2) (3HQfGeL JfejI GfJGL GdSjGQGJ (B((3Ejg Hi Oi Hi(B) (3h GdPi HOC JWHjbg YGe (B2013. (3h JfGhdJ GdOQGSI Gdgjcd GdGbJUGOi dLfhH GaQjbjG h OhQ GdbWGY GdUfGYi ajg HGdGVGag Gdi JWhQ GdSjGSGJ GdUfGYjI GdeWHbg ai bWGY UfGYI GdSjGQGJ ai LeghQjI LfhH GaQjbjG h GdJMhd ef SjGSI GdeMJhi GdeMdi Gdi SjGSGJ GdJhLg fMh GdJUOjQ h RjGOI GdefGaSI GdYGdejI h GKQ Jdc GdSjGSGJ Ydi JfejI hJWhjQ bWGY UfGYI GdSjGQGJ MjK JhUdJ GdOQGSI Gdi Cf HQfGeL (B((3Ee Bi Oi Hi(B) (3dg CKQ CjLGHjkG Ydi UGOQGJ UfGYI GdSjGQGJ ai LfhH GaQjbjG(B: (3MjK GQJaYJ UGOQGJ GdUfGYI ef (B443 (3edjhf QfO YGe (B1989: (3Gdi (B86,9 (3Hdjhf QfO YGe (B2012: (3ceG CKQJ Ydi GdhGQOGJ MjK GQJaYJ bjeI hGQOGJ GdSjGQGJ hGdechfGJ ef (B16,4 (3Hdjhf QfO YGe (B1995 (3MJi (B36,1 (3Hdjhf QfO HMdhd YGe (B2012s
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdCaQjbjI GdYdjG (B- (3bSe GdfXe GdGbJUGOjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdSjGSGJ GdUfGYjIs; (3HQfGeL JfejI h JWhjQ bWGY UfGYI GdSjGQGJs; (3UfGYI GdSjGQGJs